PSYCHOLOGICAL STRUCTURAL ANALYSIS TO â€œA CHILD CALLED ITâ€ BY DAVE PELZER - Susilowati, Endang (State Institute of Islamic Studies Salatiga, 2013)
This paper attempts to explore a child abuse, the reason and the effect of the character?s psychological development using the theory of psychological development and structural analysis. Two approaches are used in this paper. Those are structural approach and psychology, especially developmental psychology approach. The first approach focuses on literary intrinsic elements. The second approach focuses on the character?s psychological development based on the developmental stages and tasks. Those are integrated into a psychological structural analysis. The result shows that child abuse that experienced by David is physical and psychological. He got the first stage of abuse commited by his mother who didn?t give him food and the last stage evidenced by some physical abuses when he lived with his mother. The primary reasons of David abuses are disciplinary patterns and he was regarded as a trouble maker. Keywords:Psychological structural analysis; child abuse and psychological development.